Differences in Trocar Positioning within the Vertebral Body Using Two Different Positioning Methods: Effect on Trainee Performance. (25th September 2011) - Komemushi, Atsushi; Takizawa, Kenji; Tanaka, Norimitsu; Yoshimatsu, Misako; Yagihashi, Kunihiro; Ogawa, Yukihisa; Fujikawa, Atsuko; Uejima, Iwao; Koike, Yuya; Tamura, Taiji; Takahashi, Makoto; Koizumi, Jun; et al.
Abstract : Purpose . To evaluate the educational effect of the Japanese Society of Interventional Radiology 7th Academic Summer Seminar from a technical perspective. Materials and Methods . Nineteen trainees participated in the seminar. The seminar consisted of vertebroplasty trainings using swine with the single-plane landmark method and with the ISOcenter Puncture (ISOP) method. All trainees were advised by an instructor as they operated the instruments and punctured the vertebra. For each trainee, the accuracy in the final position of the needle tip of the initial puncture in each swine training was evaluated. Results . Error in the final position of the needle tip of ≥5 mm from the target puncture site occurred in the lateral direction in 42% (8/19) of trainees with the landmark method and 5% (1/19) with the ISOP method. No error ≥5 mm occurred in the vertical or anteroposterior directions. In terms of puncture accuracy, error in the lateral direction was significantly lower with the ISOP method than with the landmark method (2.2 ± 1.5 mm versus 5.6 ± 3.2 mm). Conclusion . This seminar was effective training for trocar placement for beginners. The puncture was more accurate with the ISOP method than with the landmark method.